Differences in Self-Esteem Between Cat Owners, Dog Owners, and Individuals Without Pets - Schulz, Claudia; König, Hans-Helmut; Hajek, André (Frontiers in Veterinary Science, 2020)
Introduction: Pet ownership may provide an additional source of social support and may contribute to the owner’s self-esteem. Self-esteem is considered a basic human need and is associated with psychological conditions such as depressive symptoms. To date, there is limited knowledge on the association between keeping a pet and self-esteem. Objectives: The aim of this study was to determine whether cat owners, dog owners and individuals without pets differ in terms of self-esteem, and whether there are differences between male and female owners. Methods: Data were taken from the German Ageing Survey (wave 5; nationally representative sample of individuals residing in private households ≥ 40 years). In this survey, the widely used and well-established Rosenberg scale was used to quantify self-esteem. Socioeconomic, lifestyle and health-related factors were adjusted for in the regression analysis (n=5,485). Results: Multiple linear regressions showed that dog owners reported higher self-esteem scores compared to individuals without pets (β=.04, p<.05). Similarly, male dog owners reported higher self-esteem scores compared to men without pets (β=.07, p<.01). In contrast, female cat owners reported lower self-esteem scores compared to women without pets (β=-.07, p<.01). Conclusion: Study findings showed a link between owning a cat and lower self-esteem (women), as well as between owning a dog and higher self-esteem (total sample; men). Future studies should concentrate on investigating the underlying mechanisms. Furthermore, longitudinal studies are needed to better understand the link between animal ownership and self-esteem.